In the Heart of Liberal Democracy: Whitewashing Authoritarian Surveillance a Decade After the Snowden Revelations - Ogasawara, Midori (Surveillance & Society, 2025)
Practices of authoritarian surveillance are not limited to so-called authoritarian states. Authoritarian surveillance has been increasingly witnessed in countries that uphold liberal democratic principles and institutions in the twenty-first century, along with accelerated automation of mass surveillance. This article situates authoritarian surveillance as a problem in the heart of democracy and capitalism in its materiality and imperial expansion and discusses how mass surveillance has redrawn boundaries of democratic principles. What Edward Snowden has revealed since 2013 is a good reminder of the materiality of the global surveillance networks built under the “War on Terror” that we still live in. They are embedded within digital communication infrastructures by the security agencies in the United States, the self-defined champion of liberal democracy. Nonetheless, a decade after the Snowden revelations, the authoritarian surveillance within democracy has been whitewashed in technological competitions with the Global South, such as China and India, and in tech-savvy culture in the Global North. What is the driving force of this oblivion? In a contrast with the COVID-19 pandemic surveillance, I highlight the exceptional position given to the security intelligence and policing agencies within liberal democratic institutions to generate authoritarian surveillance continuously from the imperial to postcolonial times. It is critically important to deconstruct the binary discourse of democratic states versus authoritarian states because this view tends to only problematize surveillance activities by countries located outside the “West” and sees authoritarian surveillance practiced by self-defined democratic states as harmless or even necessary to counter perceived authoritarian states. It further fuels global dissemination of surveillance technologies, just like the nuclear arms races, and produces more victims of authoritarian surveillance on earth, without borders.